The application of the Temporary Protection Directive: Challenges and good practices for Ireland - Stapleton, Amy; Dalton, Ciára (ESRI, 2024)
Temporary protection is an exceptional measure that provides immediate and temporary protection to people displaced from non-EU countries who are unable to return to their country of origin. The EU Temporary Protection Directive (TPD) was activated for the first time on 4 March 2022 following Russia’s military invasion of Ukraine. A total of 103,458 Personal Public Service Numbers had been allocated in Ireland to beneficiaries of temporary protection (BoTPs) by 31 December 2023 (Central Statistics Office [CSO], 2024). The CSO has estimated that 78 per cent of people registered for temporary protection in Ireland continued to reside in Ireland after 30 November 2023. This report explores the implementation of the TPD in Ireland, including the supports provided to BoTPs – persons who have been granted protection according to the European Council Directive 2001/55/EC – and the challenges and good practices that have presented when they seek to access particular rights under the Directive. The research period for this study is from 1 January 2023 to 31 December 2023. Developments prior to January 2023 are also included where it is considered important to understand the context and situation since the implementation of temporary protection in Ireland. Therefore, where relevant, reference is made to data or challenges concerning people from Ukraine enjoying or applying for other types of residence rights since 24 February 2022. For the research period, the main challenge for Ireland remained the continued provision of accommodation for BoTPs to the scale required. The following sections provide an overview of the key findings related to legal status and access to rights provided by the TPD.